SHIFT ON THE TRANSLATION OF ENGLISH ACTIVE CONSTRUCTIONS INTO INDONESIAN - Julianti, Defi (Universitas Gunadarma, 2013)
The purpose of this research is to find out the kinds of shift occured on the translationof English active constructions into Indonesian. This research uses a descriptivemethod that all of the data that are anlyzed are in the form of phenomenondescription and in theform of words or sentences not in theform of numbers. Thetechniques in analyzing data are editing, classification of data, presenting dataand interpretation of data. The data are taken from two sources of novels, theyare the English version which entitled The Naked face by Sidney Sheldon andIndonesian version which entitled Wajah Sang Pembunuh by Anton Adiwiyoto.Data are classified into two categories, they are: the occurrence ofshift ofEnglishactive into Indonesian active, and the occurrence of shift of English active intoIndonesian passive. The result of this research is the kinds ofshift that the writerfound are structural and rank shift.